Yield losses of soybean due to target spot (Corynespora cassiicola), its genetic and chemical management - Edwards Molina, Juan Pablo (2018)
Target spot is a foliar disease of soybean that can produce yield losses. The disease has recently become a concern due to increasing intensity of its epidemics in the main soybean growing countries (USA, Brazil and Argentina). The goals of this study were to i) estimate the target spot control efficiency and yield response of labeled fungicides for the main soybean growing region of Brazil and identify factors affecting their performance; ii) characterize the relationship between target spot severity and soybean yield using meta-analytic techniques, and to identify patterns which allow understanding the heterogeneity in the relationship; iii) to explore the variability of genetic resistance of cultivars and verify the less time-consuming methodology for doing it; iv) explore the pathogen-host interaction effects on the epidemic development; v) compare the sensitiveness of the canopy strata position injured by C. cassiicola to reduce grain yield. Fungicides containing fluxapyroxad + pyraclostrobin were the most efficient ones to control target spot, with control levels of 75% and their yield response depended on the disease pressure (DP, DPLow < 35% target spot severity at untreated checks <= DPHigh). At DPLow was unprofitable the use of fungicides and at DPHigh the latter fungicides had the best performances increasing yield relative to the untreated check in > 469 kg ha-1 (+19.1%). Potential yield of soybean in absence of target spot was estimated in 3507 kg ha-1 for 41 trials in Brazil and the percentual reduction for each target spot severity point was calculated in 0.48%, what would represent a reduction of 24% in a hypothetical target spot severity of 50% (ranging from 8% to 42%). The soybean cultivar had a significant effect to explain this wide range of responses: potential losses of 11%, 18.5% and 42% was calculated for cultivar BMX Potência RR, TMG803 and M9144RR respectively at target spot severity = 50%. We observed high variability on the genetic resistance in the tested germplasm: cultivars with very low target spot intensity (BRS360) to highly susceptible cultivars. A single-point disease severity assessment was not as reliably as an integrative three-point assessment, which had no difference with a less time-consuming two-point disease assessment. In trials where 3 C.cassicola isolates from different regions of Brazil were inoculated individually on 3 soybean cultivars contrasting in their resistance level we observed that the incubation period, disease severity, lesion density and lesion size at 14 days after inoculation, were influenced by the cultivar and not by isolate geographical origin. Using disease severity coupled with defoliation assessments throughout the reproductive growth stages, we performed correlations between grain yield and the leaf area injury at different plant positions - growth stages. The best correlation was observed with the assessments at R5.5 for injuries at middle canopy section.